Validity and diagnostics of the Reading the Mind in the Eyes Test (RMET) in non-demented amyotrophic lateral sclerosis (ALS) patients - Aiello, Edoardo Nicolò; Carelli, Laura; Solca, Federica; Torre, Silvia; Ferrucci, Roberta; Priori, Alberto; Verde, Federico; Silani, Vincenzo; Ticozzi, Nicola; Poletti, Barbara (Frontiers in Psychology, 2022)
Background The aim of this study was to explore the construct validity and diagnostic properties of the Reading the Mind in the Eyes Test (RMET) in non-demented patients with amyotrophic lateral sclerosis (ALS). Materials A total of 61 consecutive patients and 50 healthy controls (HCs) were administered the 36-item RMET. Additionally, patients underwent a comprehensive assessment of social cognition via the Story-Based Empathy Task (SET), which encompasses three subtests targeting Causal Inference, Emotion Attribution (SET-EA), and Intention Attribution (SET-IA), as well as global cognitive [the Edinburgh Cognitive and Behavioral ALS Screen (ECAS)] and behavioral screening [the Frontal Behavioral Inventory (FBI); the Dimensional Apathy Scale (DAS); the Beck Depression Inventory (BDI); and the State and Trait Anxiety Inventory-Y]. The construct validity of the RMET was tested by regressing it within a stepwise model that encompassed as predictors the abovementioned cognitive and behavioral measures, covarying for demographic and motor confounders. Receiver-operating characteristics (ROC) analyses allowed exploring intrinsic and post-test properties of the RMET both in discriminating patients from HCs and in identifying patients with a defective SET-EA performance. Results The RMET was solely predicted by the SET-EA (p = 0.003) and SET-IA (p = 0.005). RMET scores showed high accuracy both in discriminating patients from HCs (AUC = 0.81) and in identifying patients with a defective SET-EA score (AUC = 0.82), with adequate-to-optimal both intrinsic and post-test properties. Discussion The RMET is a convergently and divergently valid measure of affective social cognition in non-demented ALS patients, also featuring optimal intrinsic and post-test diagnostic properties in both case-control and case-finding scenarios.